(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Foreign language lexical area in literary works of Y. Kononenko, M. Matios, S. Majdanska is observed. Also its role is established in the showing of author’s intention, heroes` individualization and ethnographical identification, stylistic functions of foreign language lexical area are determined.